The time-course of information alignment, split by first and second experiment half. - Denise Moerel (9080849) (2025)
(A) The time-course of the information alignment between the two participants in each pair for the first experiment half (light blue), and the second experiment half (purple). The shaded areas around the plot lines show the 95% confidence intervals. Cluster corrected p values <.05 are shown below the plot in the same colors. (B) The difference in information alignment between the real pairs and pseudo-pairs (real—pseudo). This shows the alignment that is not driven by visual information. All plotting conventions are the same as Fig 4A.